Corporate governance and earnings management: incentives in Malaysian IPO companies / Aida Hazlin Ismail and Norman Mohd Saleh - Ismail, Aida Hazlin; Mohd Saleh, Norman (2012)
The main objective of this paper is to investigate the relationship between audit quality (measured by auditor size) and corporate governance mechanism (Audit committee and Board of Director) impact on earnings management for IPO companies in Malaysia. This current study employs the modified Jones model 1995. The findings reveal that the audit quality proxy by auditor size does not have any significant relationship with earnings management for IPO companies in Malaysia. In addition, the independence of audit committee and total number of non-executive directors has positive relationship with earnings management. The possible reasons are management dominance over board matters and lack of knowledge among the directors on the daily affairs of the company. Therefore, results of this study provide useful information for the accounting literature and practitioners on the effective practice of corporate governance mechanism (audit committee and Board of Directors) and the choice of auditors in Malaysian IPO companies.